Tabaco en Colombia : costos y ¿beneficios? (2014)
This document analyzes the cost on the health system snuff consumption and compared these with the benefits obtained as employment and tax revenues in the period 1973-2008, this analysis is done from the estimation of quantitative by simple regression models and simultaneous equations model. Estimates of the conditional demand factors indicate that the tobacco industry has its own inertial dynamics, suggesting employability dynamics derived from industrial organization. Additionally, revenue generated by industrial and agricultural jobs in the tobacco industry can be funded with a fraction of the resources spent on health care consumers snuff